Cross-population variation in usage of a call combination: evidence of signal usage flexibility in wild bonobos - Isaac Schamberg; Martin Surbeck; Simon W. Townsend (Animal Cognition)
Abstract The arbitrary relationship between signifier and signified is one of the features responsible for language’s extreme lability, adaptability, and expressiveness. Understanding this arbitrariness and its emergence is essential in any account of the evolution of language. To shed light on the phylogeny of the phenomenon, comparative data examining the relationship between signal form and function in the communication systems of non-humans is central. Here we report the results of a study on the production and usage the whistle-high hoot call combination (W + HH) from two distant populations of wild bonobos (Pan paniscus): Lui Kotale, DRC, and Kokolopori, DRC. We find that the context in which bonobos produce the W + HHs varies systematically between populations. Our results suggest that variation in W + HH production may represent an example of signal-adjustment optionality, a key component of arbitrariness.